Seamless holographic image generation for a multi-vision system. Issue 4 (2nd October 2022) - Moon, Woonchan; Jeon, Hosung; Park, Sungjae; Kim, Soobin; Kim, Hwi; Hahn, Joonku
Abstract : This paper investigates the optical seamlessness of a holographic multi-vision display. The purpose of the multi-vision approach is to scale up the resolution of a holographic display without requiring a single extremely high-resolution spatial light modulator. Optical experiments reveal that a holographic multi-vision system with 16M pixel resolution successfully generates a seamless virtual reference plane with the essential optical characteristics of a holographic display, such as the accommodation effect and binocular parallax. It is realized from a matrix of eight (4 × 2) high-resolution transmission-type liquid crystal displays. Theoretical analysis and numerical simulations are presented for the proposed seamless holographic multi-vision system.